Channel anti-freezing and anti-seepage structure containing phase-change thermal insulation material and modified rubber concrete and construction method of channel anti-freezing and anti-seepage structure

By using phase change insulation materials and modified rubber concrete in the water transmission channel, the frost-resistant and anti-seepage problems of traditional materials under severe cold conditions are solved, and efficient water resource utilization and environmental protection are achieved.

CN119777322AActive Publication Date: 2025-04-08SINOHYRDO ENG BUREAU 3 CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411960121.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the water transmission channels in the northwest region, traditional materials are prone to freezing and damage to anti-seepage structures under severe cold conditions, resulting in waste of water resources and increased maintenance costs.

Method used

The channel anti-freeze-proof structure containing phase change insulation materials and modified rubber concrete is adopted. The structure consists of a sand and gravel cushion layer, a one-way drainage composite geomembrane, a low-temperature phase change energy storage insulation mortar, leveling mortar and a modified rubber concrete prefabricated layer, combined with a multi-row anti-seepage and anti-silt drainage and pressure relief device that runs through.

Benefits of technology

This structure has excellent insulation performance, compressive strength and waterproof performance in low temperature environments. It can effectively resist the low temperature environment, delay the icing process, improve the anti-freeze performance, and reduce the pollution of waste rubber tires to the environment, achieving efficient recycling of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777322A_ABST
    Figure CN119777322A_ABST
Patent Text Reader

Abstract

The invention discloses a channel anti-freezing and anti-seepage structure containing a phase-change thermal insulation material and modified rubber concrete, the channel anti-freezing and anti-seepage structure has an arc-bottom trapezoidal section and comprises five layers, namely a sand gravel cushion layer, a one-way drainage composite geomembrane, low-temperature phase-change energy-storage thermal insulation mortar, leveling mortar and a modified rubber concrete prefabricated layer in sequence from bottom to top; a plurality of rows of anti-seepage and anti-clogging drainage pressure relief devices are further arranged in the structure in a penetrating mode. The invention also provides a preparation method of the low-temperature phase-change energy-storage thermal insulation mortar and the modified rubber concrete precast block. The low-temperature phase-change energy-storage thermal insulation mortar has excellent phase-change energy storage, thermal insulation and waterproof performance; the modified rubber concrete precast block has good impact resistance, low elastic modulus and freezing resistance. The anti-freezing and anti-seepage capacity of the channel is effectively improved through the anti-freezing and anti-seepage synergistic effect of the five-layer structure, the resistance to frost heaving stress is particularly enhanced, and long-term stability and safety of the anti-freezing and anti-seepage structure of the channel in various complex environments are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of channel structures, and in particular relates to a channel antifreeze and anti-seepage structure containing phase change thermal insulation material and modified rubber concrete and a construction method. Background Art

[0002] In the severe cold regions of northwest my country, water transfer channels, as key infrastructure for water resource management, ensure the rational allocation and efficient use of water resources, effectively address the problem of uneven distribution and shortage of water resources in the region, and provide solid support for water resource security, agricultural prosperity, ecological balance and economic development. However, under specific climatic conditions and agricultural production needs, the channels have to continue to operate in severe cold. Due to the effects of expansion, frost heave and freeze-thaw cycles, the channel structure will suffer a lot of damage, and cracks and frost heave will appear on the surface of the anti-seepage project. Especially when the low temperature and freezing last for a long time, the frost heave damage is more serious, which not only accelerates the aging process of the anti-seepage project, but also destroys the anti-seepage structure, resulting in water resource waste and increased maintenance costs. Therefore, in view of this special operating condition, it is crucial to explore more durable and adaptable channel lining materials and technologies to ensure the long-term stable operation of water transfer channels in the northwest region.

[0003] In 2023, my country will produce about 350 million waste tires, equivalent to a weight of about 12 million tons, and the standardized disposal volume will be about 220 million tires. The standardized resource utilization rate accounts for 62%, which is far lower than the utilization level of waste plastics, waste paper and waste textiles. my country is a country with scarce rubber resources. Making full use of waste rubber is not only an effective supplement to my country's rubber resources, but also an effective way to turn waste rubber from harm to benefit. Therefore, by utilizing the elasticity and energy dissipation characteristics of waste tires, after proper treatment, they are introduced into concrete materials to develop high-performance concrete materials with large energy absorption, fatigue resistance and excellent durability. However, the industrial rubber particles produced by the traditional waste rubber tire processing method are an organic tough particle aggregate with large deformation, low density, lipophilic and hydrophobic surface and easy aggregation. It has poor compatibility with cement paste. If it is directly used for the preparation of inorganic brittle concrete materials, it will have a significant negative impact on the working performance, mechanical properties, and microscopic mechanism of the concrete mixture, and the advantages of the combination of the two are difficult to give full play. Therefore, scientific treatment of the rubber surface to ensure good bonding and synergy between the rubber aggregate and the concrete matrix is ​​an urgent problem to be solved in rubber concrete.

[0004] Expanded perlite is widely used in building insulation and other fields due to its low thermal conductivity. However, expanded perlite is not effective in regulating indoor temperature fluctuations caused by seasonal changes, and its thermal insulation performance is greatly limited. Therefore, as a traditional thermal insulation material, expanded perlite can no longer meet the current thermal insulation technology's demand for efficient coordination of energy in time and space. By utilizing the porous and strong adsorption characteristics of expanded perlite to store phase change materials in its gaps, and then preparing thermal insulation mortar, the energy in the environment can be stored in the form of latent heat of phase change, and this energy can be released when needed. The mortar not only has thermal insulation performance, but also has the ability to store heat and adjust temperature, realizing the conversion of energy between different times and spaces. In the cold winter, the energy from direct sunlight is stored and heat is released to increase the indoor temperature, which greatly reduces energy consumption and achieves energy conservation and emission reduction.

[0005] Traditional channel construction methods often have problems such as long construction period, difficult quality control, and high maintenance costs, which are difficult to meet the needs of modern agriculture for high efficiency, water conservation, and environmental protection. Precast concrete blocks have broad application prospects in channel construction due to their stable quality, fast construction speed, energy conservation, and reduced environmental pollution. They are of great significance in improving water resource utilization efficiency, promoting agricultural modernization, promoting the development of green buildings, and reducing maintenance costs.

[0006] Therefore, a channel antifreeze and anti-seepage structure and a construction method containing phase change thermal insulation material and modified rubber concrete are needed. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a channel antifreeze and anti-seepage structure containing phase change thermal insulation materials and modified rubber concrete in view of the deficiencies of the above-mentioned prior art. The present invention sequentially arranges a gravel cushion layer, a one-way drainage composite geomembrane, a low-temperature phase change energy storage thermal insulation mortar, a leveling mortar and a modified rubber concrete prefabricated layer to form an arc-bottomed trapezoidal section, and the bottom is designed as an arc-bottomed trapezoidal section to enhance the stability and adaptability of the overall structure. The channel antifreeze and anti-seepage structure integrates a plurality of rows of anti-seepage, anti-clogging and drainage pressure relief devices to discharge excess pressure water at the bottom of the channel to ensure the long-term stability and safety of the channel antifreeze and anti-seepage structure in various complex environments.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete, characterized in that the channel antifreeze and anti-seepage structure is an arc-bottom trapezoidal cross-section and includes 5 layers, from bottom to top, a gravel cushion layer, a one-way drainage composite geomembrane, a low-temperature phase change energy storage insulation mortar, a leveling mortar and a modified rubber concrete prefabricated layer; the channel antifreeze and anti-seepage structure is penetrated by multiple rows of anti-seepage, anti-blocking and drainage pressure relief devices.

[0009] The channel antifreeze and anti-seepage structure of the present invention is a structure with an arc-bottom trapezoidal cross-section formed by sequentially arranging a gravel cushion layer, a one-way drainage composite geomembrane, a low-temperature phase change energy storage thermal insulation mortar, a leveling mortar and a modified rubber concrete prefabricated layer in the channel. The bottom is designed as an arc-bottom trapezoidal cross-section to enhance the stability and adaptability of the overall structure. The channel antifreeze and anti-seepage structure is integrated with a plurality of rows of seepage-proof and anti-clogging drainage and pressure relief devices to discharge excess pressure water at the bottom of the channel to ensure the long-term stability and safety of the channel antifreeze and anti-seepage structure in various complex environments. The low-temperature phase Variable energy storage insulation mortar has excellent thermal insulation performance, good compressive strength and waterproof performance, and can automatically absorb heat and release heat to effectively resist low temperature environment, effectively delay the freezing process and improve the antifreeze performance of the material; the modified rubber concrete precast layer, with its outstanding mechanical properties, impact resistance, low elastic modulus and excellent antifreeze performance, has become the preferred solution for channel frost heave stress in the western region with large temperature difference and cold environment, reducing the pollution of waste rubber tires to the environment and achieving the dual goals of efficient recycling of waste resources and environmental protection.

[0010] The present invention combines a modified rubber concrete prefabricated layer with a low-temperature phase-change energy storage insulation mortar, optimizes the channel's anti-freeze and anti-seepage structure, and uses a full-section modified rubber concrete prefabricated layer lining scheme to arrange an arc-bottomed trapezoidal section, thereby greatly improving the channel structure's anti-freeze heaving and anti-seepage performance, and can also solve the problem of easy frost heaving and cracking at the corners of traditional flat-bottomed sections. In addition, based on the arc-bottomed trapezoidal section of the modified rubber concrete prefabricated layer, it also has certain advantages in terms of construction cost and construction efficiency. Applying this technology to water conveyance channel lining projects in the severely cold regions of the northwest not only makes full use of waste rubber resources, rationally utilizes resources and reduces environmental pollution, but is also expected to provide a more reliable, environmentally friendly and economical solution for water conveyance channel projects in the northwest region, and further promote the efficient utilization and rational allocation of water resources.

[0011] It should be noted that the anti-seepage and anti-clogging drainage and pressure relief device is an anti-clogging check valve.

[0012] The above-mentioned channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete is characterized in that the thickness of the gravel cushion layer is 10cm-20cm, the thickness of the one-way drainage composite geomembrane is 2mm-3mm, the thickness of the low-temperature phase change energy storage insulation mortar is 6cm-10cm, the thickness of the leveling mortar is 2mm-3mm, the thickness of the modified rubber concrete prefabricated layer is 7.0cm-10.0cm, and the modified rubber concrete prefabricated layer includes a channel slope arranged on the channel slope prefabricated blocks and arc-shaped channel bottom prefabricated blocks arranged on the channel bottom; two rows of staggered anti-seepage and anti-siltation drainage and pressure relief devices are arranged on each side of the channel slope of the channel anti-freezing and anti-seepage structure, and a row of anti-seepage and anti-siltation drainage and pressure relief devices is arranged in the middle part of the channel bottom of the channel anti-freezing and anti-seepage structure, and the spacing between the anti-seepage and anti-siltation drainage and pressure relief devices in the same row is 10m to 15m, one row of anti-seepage and anti-siltation drainage and pressure relief devices on each side of the channel slope is 50cm to 60cm high from the slope foot, and the other row is 50cm to 60cm below the normal water level of the channel.The present invention provides a stable foundation for the upper structure by setting a gravel cushion layer and controlling its thickness, thereby improving the bearing capacity of the foundation, reducing foundation settlement, accelerating the drainage and consolidation of the soft soil layer, and having a certain thermal insulation property to prevent frost heave; by setting a one-way drainage composite geomembrane and controlling its thickness, moisture penetration is prevented, and its one-way drainage performance ensures that moisture can be discharged smoothly, effectively isolates moisture, and improves the anti-seepage performance of the channel; by setting a low-temperature phase change energy storage insulation mortar and controlling its thickness, the phase change energy storage principle is utilized to absorb or release heat when the temperature fluctuates, thereby improving the thermal insulation performance of the channel, reducing energy loss, and also helping to prevent frost heave damage, and is particularly suitable for cold areas, and the requirements of thermal insulation and energy storage are fully met by controlling the thickness, and the anti-frost heave effect is the same as the thermal insulation effect of replacing 50cm to 60cm thick gravel, which can effectively reduce the thickness of the gravel cushion layer, reduce the amount of engineering, and save construction period; by setting a leveling mortar and controlling its thickness, the flatness and Stability helps to reduce the stress concentration phenomenon caused by unevenness; by setting a modified rubber concrete prefabricated layer as the main structural part of the channel, it bears the impact of water flow and load. Its prefabrication helps to speed up the construction speed and improve the quality of the project. It has the characteristics of high strength, good durability, and convenient construction. By controlling its thickness, it can meet the structural strength requirements and maintain a light weight, which is convenient for transportation and installation, ensuring the long-term stable operation of the channel. In addition, by dividing the modified rubber concrete prefabricated layer into a channel slope prefabricated block set on the channel slope and an arc-shaped channel bottom prefabricated block set on the channel bottom, it is convenient to prefabricate and improve the convenience of construction. By controlling the installation position of the anti-seepage, anti-clogging and drainage pressure relief device, it is convenient to drain water and ensure the performance of the channel anti-freezing and anti-seepage structure. The present invention can give full play to the respective advantages through the combination of the above structures, forming a channel anti-freezing and anti-seepage structure with multiple functions such as anti-seepage, drainage, thermal insulation and anti-freezing, high strength and stability, and improving the overall performance and service life of the channel.

[0013] The above-mentioned channel antifreeze and anti-seepage structure containing phase change thermal insulation material and modified rubber concrete is characterized in that the preparation method of the low-temperature phase change energy storage thermal insulation mortar comprises the following steps:

[0014] Step 1, preparing calcined expanded perlite: calcining the expanded perlite in stages to obtain calcined expanded perlite;

[0015] Step 2, preparing a composite phase change energy storage material: heating propylene glycol, KCl, Al(NO3)3 and H2O in a water bath and blending them, then adding SrCl2 as a nucleating agent and performing ultrasonic dispersion to obtain a composite phase change energy storage material;

[0016] Step 3, preparing phase-change expanded perlite: pouring the composite phase-change energy storage material obtained in step 2 into a suction filtration bottle and heating it in a water bath, then pouring the calcined expanded perlite obtained in step 1 into the suction filtration bottle, and then vacuumizing the suction filtration bottle, and finally cooling it at room temperature to obtain phase-change expanded perlite;

[0017] Step 4, surface treatment of vitrified microspheres and phase-change expanded perlite: the vitrified microspheres and the phase-change expanded perlite obtained in step 3 are placed in a mixer for stirring respectively, and while stirring, the silane coupling agent is evenly sprayed on the surface of the phase-change expanded perlite and the vitrified microspheres through an ultrasonic atomizing nozzle. After the spraying is completed, the sprayed vitrified microspheres and the phase-change expanded perlite are taken out and placed in a dryer for aging respectively, to obtain surface-treated vitrified microspheres and surface-treated phase-change expanded perlite respectively;

[0018] Step 5. Preparation of low-temperature phase-change energy storage and thermal insulation mortar: Put the glue powder and water into a weightless mixer and stir for more than 60 seconds, then add the surface-treated vitrified microspheres and surface-treated phase-change expanded perlite obtained in step 4 at a speed of 40rpm to 60rpm, stir for 3min to 5min, and obtain a low-temperature phase-change energy storage and thermal insulation mortar with a consistency of 70mm to 90mm; the low-temperature phase-change energy storage and thermal insulation mortar is composed of the following components in parts by mass: glue powder 170-180 parts, surface-treated vitrified microspheres and surface-treated phase-change expanded perlite 120-130 parts, the mass ratio of water to rubber powder is 0.7-0.9:1, and the volume ratio of the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite is 6-7:3-4; the rubber powder is composed of the following components in mass parts: 136-144 parts of cement, 25.5-27 parts of fly ash, 8.5-9 parts of slaked lime, 1.36-1.44 parts of Wacker latex powder 4015N, 0.34-0.36 parts of hydroxypropyl methylcellulose, 0.136-0.144 parts of triethanolamine, 0.34-0.36 parts of sodium methyl siliconate, and 0.7-1.0 parts of polypropylene fiber.

[0019] The present invention prepares calcined expanded perlite with complete expansion and more uniformly arranged pore structure by calcining expanded perlite in stages; the present invention uses organic and inorganic phase change materials for compounding, i.e., propylene glycol, KCl, Al(NO3)3 and H2O are mixed by water bath heating, so as to improve the problems of low latent heat and low thermal conductivity of propylene glycol, and make up for the shortcomings of large supercooling and easy phase separation of KCl and Al(NO3)3, optimize the phase change temperature and latent heat of the material, form a material with higher energy storage density, thereby improving the energy storage performance of the material; SrCl2 is used as a nucleating agent to promote uniform dispersion of the material and enhance the thermal stability and molecular stability of the material; the present invention uniformly infiltrates the composite phase change energy storage material into the pore structure of the calcined expanded perlite, and firmly combines the composite phase change energy storage material on the calcined expanded perlite by vacuuming and cooling solidification, thereby preparing the expanded perlite with phase change energy storage function; the present invention adopts ultrasonic atomization spraying Silane coupling agent has stable and efficient spraying effect, and can quickly form a thin film on the surface of glass microspheres and phase change expanded perlite, thereby improving its waterproofness, wear resistance and anti-aging performance, and improving its bonding performance with other materials; the rubber powder of the present invention is mainly composed of cement, fly ash, slaked lime, etc., and the added Wacker latex powder, hydroxypropyl methylcellulose, triethanolamine, and sodium methylsiliconate components can enable the perlite mortar to form a tight and interwoven mesh film structure after hardening, which significantly enhances the bonding force between rubber particles and cement-based materials, not only optimizes the overall structure of the thermal insulation mortar, but also greatly improves its flexibility; polypropylene fibers are randomly distributed in the mortar to form an effective network winding structure, which effectively prevents slippage between aggregates, thereby reducing the generation of cracks; and a gravity-free mixer is used for stirring, which can ensure that the material is not affected by the difference in particle size and specific gravity during the mixing process by virtue of its unique mixing technology, thereby achieving an efficient and uniform mixing effect.

[0020] The above-mentioned channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete is characterized in that the process of segmented calcination in step 1 is: heating to 400°C at a heating rate of 10°C / min to 20°C / min, then keeping warm for 0.5h to 1h, then heating to 800°C at a heating rate of 10°C / min to 20°C / min, then keeping warm for 0.5h to 1h, then heating to 850°C to 1000°C at a heating rate of 5°C / min to 10°C / min, then keeping warm for 1h to 2h, and finally cooling to room temperature. The present invention prepares expanded perlite with complete expansion and more uniform arrangement of pore structure by controlling the parameters of segmented calcination.

[0021] The above-mentioned channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete is characterized in that the mass ratio of glycerol, KCl, Al(NO3)3 and H2O in step 2 is 1-1.5:1.0-1.5:2.0-2.5:4.5-5.8, the amount of SrCl2 added is 1%-2% of the total mass of glycerol, KCl, Al(NO3)3 and H2O, the temperature of the water bath heating blending is 50°C-60°C, and the time of the ultrasonic dispersion is 0.5h-1h. The present invention ensures that the composite phase change energy storage material has the best performance by controlling the composition and configuration parameters of the composite phase change energy storage material.

[0022] The above-mentioned channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete is characterized in that the temperature of the water bath heating in step 3 is 50°C to 60°C, the pressure of the vacuum pumping is -0.05MPa to -0.07MPa, the time is 10min to 20min, and the cooling time is more than 24h. The present invention ensures that the phase change expanded perlite has the best performance by controlling the parameters of preparing the phase change expanded perlite.

[0023] The above-mentioned channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete is characterized in that the stirring speed in step 4 is 40rpm-60rpm, the time is 3min-5min, the silane coupling agent is KH550 or KH570, and the aging time is more than 48h. The present invention controls the stirring parameters to evenly spray the silane coupling agent on the surface of the glass microspheres and the phase change expanded perlite.

[0024] The above-mentioned channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete is characterized in that the modified rubber concrete prefabricated layer is made of the following components in parts by mass: 153-157 parts of water, 274-292 parts of cement, 73-91 parts of fly ash, 654-730 parts of sand, 1180-1190 parts of gravel, 4.198-4.445 parts of water reducer, 0.517-0.531 parts of air entraining agent and 39-115 parts of modified rubber powder.

[0025] The above-mentioned channel antifreeze and anti-seepage structure containing phase change thermal insulation material and modified rubber concrete is characterized in that the preparation method of the modified rubber powder comprises the following steps:

[0026] Step 1: Sorting and crushing of waste rubber: crushing and separating the waste rubber to obtain rubber powder with a particle size less than 16 mesh;

[0027] Step 2, cleaning: soak the rubber powder obtained in step 1 in clean water for 6h to 8h, and mechanically stir for 10min every 2h to 3h, then take it out and soak it in 1.0mol / L to 2.0mol / L NaOH solution for 24h, and mechanically stir for 10min every 4h to 6h, then wash it to neutrality and dry it;

[0028] Step 3, ultrasonic desulfurization activation treatment: the rubber powder dried in step 2 is activated by an ultrasonic energy-focusing transducer at a frequency of 20kHz to 50kHz for 10min to 20min, and then aged in a dry environment for 6h to 10h to obtain desulfurized activated rubber powder;

[0029] Step 4, preparation of hydrophilic rubber powder: the desulfurized activated rubber powder obtained in step 3 and the dispersant solution are mixed at a mass and volume ratio of 900-1100:200-400, the mass unit is g, and the volume unit is mL, wherein the mass of the dispersant is 1%-3% of the mass of the desulfurized activated rubber powder, and then heated to 60°C-100°C, and stirred at a stirring speed of 150rpm-200rpm for 2min-5min, then a modifier is added, stirred for 30min-50min, and the product is washed to obtain hydrophilic rubber powder; the modifier is three or more of maleic anhydride, acrylic acid, sodium methacrylic acid, urea, sodium polystyrene sulfonate, ammonium persulfate, and mercaptopropionic acid;

[0030] Step 5, inorganic encapsulation modification: put the hydrophilic rubber powder obtained in step 4 and the inorganic modified admixture in a volume ratio of 3 to 5:1 into an air flow stirring device, mix and stir for 10 to 20 minutes, and then age for 24 hours to obtain modified rubber powder; the inorganic modified admixture is ultrafine silicon powder, metakaolin and phosphorus slag powder in a mass ratio of 2 to 3:3 to 4:3 to 4.

[0031] The present invention obtains small-particle rubber powder by crushing, removes impurities such as oil, dust, organic matter and the like on the surface of the rubber powder by cleaning, improves the roughness and hydrophilicity of the surface of the rubber powder, and improves the interfacial bonding performance between the rubber powder and cement; through ultrasonic desulfurization and activation treatment, the acoustic energy directly acts on the rubber powder to cavitate it, destroys the CS bond and SS bond in the rubber powder whose energy is lower than that of the CC bond, selectively destroys the three-dimensional network structure, realizes desulfurization and regeneration, and the physical and mechanical properties of the desulfurized and activated rubber powder after vulcanization are similar to those of the original rubber material, and has the advantages of high product quality, no pollution, low energy consumption and the like;

[0032] The present invention uses a dispersant to prevent the desulfurized activated rubber powder from agglomerating and to disperse it more evenly in a solution; the main component of the desulfurized activated rubber powder is polyisoprene, which contains a large amount of unsaturated double bonds, so that the rubber particles are hydrophobic, the adhesion between the rubber particles and the cement substrate is relatively low, and there are relatively serious defects on the interface, resulting in the rubber concrete having a low elastic modulus, large deformation and reduced compressive strength; the C=C on the surface of the rubber particles is broken by a chemical modification method, and hydrophilic groups such as -CO-, -OH and -SO3H are introduced, and orientation forces between polar molecules and polar molecules are added between the contact surfaces of the rubber and concrete materials, so that the two are more closely combined, and various properties of the modified rubber concrete prefabricated layer are enhanced, and at the same time, the oleophilic and hydrophobic properties of the rubber powder surface are solved, and the rubber concrete is not oleophilic or hydrophobic. The problem of inorganic admixtures floating easily in concrete; the present invention uses air flow to mix, disperse and refine inorganic admixtures with hydrophilic rubber powder in the air flow, and embeds it into the hydrophilic rubber powder through complex stress effects such as shearing, impact and stirring. The inorganic powder is evenly distributed in the cracks and pores of the hydrophilic rubber powder, and forms adsorption and embedding effects with the hydrophilic rubber powder, which greatly avoids the occurrence of mixed mixture bleeding and stratification and uneven components after hardening when it is used as concrete aggregate, and forms an inorganic coating layer on the surface of the hydrophilic rubber powder, thereby improving the dispersibility of the modified rubber powder in concrete, avoiding the occurrence of modified rubber powder agglomeration, and enhancing the interface bonding force between the modified rubber powder and the concrete matrix, thereby improving the mechanical properties of the modified rubber concrete precast layer.

[0033] In addition, the present invention also provides a construction method for a channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete, characterized in that the method comprises the following steps:

[0034] Step 1: Measure and lay out: Use a total station to measure and lay out;

[0035] Step 2: Channel base surface treatment: excavate a trapezoidal channel according to the measurement and layout in step 1;

[0036] Step 3: Laying gravel cushion layer: Laying gravel cushion layer in the trapezoidal channel excavated in step 2;

[0037] Step 4: Arrange anti-seepage and anti-clogging drainage and pressure relief devices: Arrange anti-seepage and anti-clogging drainage and pressure relief devices in the gravel cushion layer laid in step 3;

[0038] Step 5: Laying and splicing one-way drainage composite geomembrane: Laying and splicing one-way drainage composite geomembrane on the gravel cushion after the anti-seepage, anti-clogging and drainage pressure relief device is arranged in step 4;

[0039] Step 6: Apply low-temperature phase-change energy storage thermal insulation mortar: Apply low-temperature phase-change energy storage thermal insulation mortar on the spliced ​​one-way drainage composite geomembrane laid in step 5;

[0040] Step 7: Spread the modified rubber concrete prefabricated layer, apply leveling mortar on the low-temperature phase change energy storage insulation mortar applied in step 6, and then spread the modified rubber concrete prefabricated layer on the leveling mortar;

[0041] Step 8: Surface inspection and anti-seepage treatment: Inspect the prefabricated modified rubber concrete layer spread in step 7, and apply polyvinyl chloride glue to the defective parts;

[0042] Step nine, maintenance and acceptance: the structure coated with polyvinyl chloride mortar in step eight is maintained, and then accepted to obtain a channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete.

[0043] Compared with the prior art, the present invention has the following advantages:

[0044] 1. The present invention sequentially arranges a gravel cushion layer, a one-way drainage composite geomembrane, a low-temperature phase change energy storage insulation mortar, a leveling mortar and a modified rubber concrete prefabricated layer to form a channel antifreeze and anti-seepage structure with an arc bottom trapezoidal cross-section. The bottom is designed as an arc bottom trapezoidal cross-section to enhance the stability and adaptability of the overall structure. The channel antifreeze and anti-seepage structure is integrated with a plurality of rows of seepage and anti-clogging drainage and pressure relief devices to discharge excess pressure water at the channel base, so as to ensure the long-term stability and safety of the channel antifreeze and anti-seepage structure in various complex environments.

[0045] 2. The low-temperature phase change energy storage insulation mortar of the present invention has excellent thermal insulation performance, good compressive strength and waterproof performance, and can automatically absorb heat and release heat to effectively resist low temperature environment, effectively delay the freezing process and improve the antifreeze performance of the material. The modified rubber concrete precast layer, with its excellent mechanical properties, impact resistance, low elastic modulus and excellent antifreeze performance, has become the preferred solution for channel frost heave stress in the western region with large temperature difference and cold environment, reducing the pollution of waste rubber tires to the environment, and achieving the dual goals of efficient recycling of waste resources and environmental protection. The channel antifreeze and anti-seepage structure has a high degree of production standardization and construction quality, which improves construction efficiency.

[0046] 3. The present invention utilizes waste rubber tire particles and innovatively prepares modified rubber powder by combining physical-chemical modification with inorganic material coating technology. The modified rubber powder shows good compatibility with cement-based materials, effectively avoids the floating stratification phenomenon, and ensures the stability of the interface. Compared with traditional concrete, the concrete prepared with this modified rubber powder has excellent performance in crack resistance and impact resistance, and at the same time has a lower elastic modulus and excellent freeze-thaw resistance. It can not only effectively deal with the frost heave stress problem caused by the large temperature difference and cold environment in the western region to the channel, but also can significantly reduce the pollution of waste rubber tires to the environment, achieving the dual goals of effective utilization of waste resources and environmental protection.

[0047] 4. The present invention prepares an inorganic-organic composite low-temperature phase change energy storage insulation mortar, which has good energy storage performance and has the advantages of composite materials. It effectively overcomes the shortcomings of single-type phase change materials, such as low thermal conductivity, low phase change latent heat, supercooling and phase separation. The strong adsorption performance of expanded perlite is used to absorb phase change materials, and a vacuum impregnation process is adopted to prepare a vitrified microsphere-expanded perlite-based composite low-temperature phase change insulation material. It can not only automatically adjust the temperature to maintain a stable environment in the channel, but also achieve heat storage and energy saving, and improve energy utilization efficiency. When the ambient temperature drops to near the freezing point, the phase change material will begin to undergo phase change to release heat, thereby reducing damage caused by freezing, and can effectively delay the freezing process and improve the material's antifreeze performance. Higher insulation effect can effectively reduce the thickness of the gravel layer by more than 30 cm, increase the channel cross-sectional area, and increase the flow rate. The material is safe, reliable, green and environmentally friendly, and is easy to construct. It is compatible with traditional building materials, which not only helps to improve the operating efficiency and safety of the channel, but also effectively reduces the maintenance cost. It is an ideal choice for channel insulation.

[0048] 5. The drainage system composed of a check valve of the present invention realizes a one-way drainage function by utilizing the fluctuation of water levels in the channel and under the channel base. The system can prevent infiltration into the channel base during the channel operation period, and discharge the water infiltrating the channel base into the channel in a one-way manner during the channel water outage period. This can effectively reduce the water level under the channel base, ensure the stability of the structure, and actively reduce the damage caused by excessive osmotic pressure due to leakage in the channel.

[0049] 6. The present invention adopts an arc-bottom trapezoidal section design of a full-section modified rubber concrete prefabricated layer lining. The arc-bottom trapezoidal section has no obvious stress angle at the reverse arch arc bottom. When a slight frost heave occurs in the arc bottom gravel cushion layer, it can ensure uniform force and avoid cracking and bulging due to excessive local stress concentration. It has better anti-frost heave performance, not only reduces leakage, and the arc-bottom design optimizes water flow conditions to increase water flow, but also solves the problem of easy frost heave and cracking at the corners of traditional flat-bottom sections. The production of prefabricated blocks is highly standardized, which not only ensures the consistency of construction quality, but also greatly shortens the on-site construction time, improves construction efficiency, and saves construction costs. It also shows obvious advantages. It is an advanced technical solution worthy of promotion in modern water conservancy projects.

[0050] 7. The modified rubber concrete prefabricated layer material of the present invention has high strength, good erosion resistance and frost resistance, and has improved toughness and ductility, which to a certain extent improves the deformation resistance of the concrete channel antifreeze and anti-seepage structure. It is produced by designed and formed molds, which not only has high integration, but also has guaranteed quality and good appearance. It can be mass-produced and greatly improves the construction progress.

[0051] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a structural schematic diagram of a channel antifreeze and anti-seepage structure containing phase change thermal insulation material and modified rubber concrete of the present invention.

[0053] Figure 2 yes Figure 1 Enlarged view of point A.

[0054] Figure 3 It is a structural schematic diagram of the channel slope prefabricated blocks and the channel bottom prefabricated blocks in the modified rubber concrete prefabricated layer of the present invention.

[0055] Description of reference numerals:

[0056] 1—sand and gravel cushion layer; 2—one-way drainage composite geomembrane; 3—low-temperature phase change energy storage and thermal insulation mortar;

[0057] 4—leveling mortar; 5—modified rubber concrete prefabricated layer; 6—anti-seepage, anti-clogging, drainage and pressure relief device;

[0058] 7—channel slope prefabricated block; 8—channel bottom prefabricated block. DETAILED DESCRIPTION

[0059] Figure 1 Schematic diagram of the structure of the channel antifreeze and anti-seepage structure containing phase change thermal insulation material and modified rubber concrete of the present invention, Figure 2 yes Figure 1 A magnified image, from Figure 1 and Figure 2 It can be seen that the channel antifreeze and anti-seepage structure has an arc-bottom trapezoidal cross-section and includes 5 layers, which are, from bottom to top, a gravel cushion layer 1, a one-way drainage composite geomembrane 2, a low-temperature phase change energy storage insulation mortar 3, a leveling mortar 4 and a modified rubber concrete precast layer 5; multiple rows of anti-seepage, anti-clogging and drainage pressure relief devices 6 are arranged throughout the channel antifreeze and anti-seepage structure.

[0060] Figure 3 It is a schematic diagram of the structure of the channel slope prefabricated block and the channel bottom prefabricated block in the modified rubber concrete prefabricated layer of the present invention. Figure 3 It can be seen from the figure that the modified rubber concrete prefabricated layer 6 includes a channel slope prefabricated block 7 arranged on the channel slope and an arc-shaped channel bottom prefabricated block 8 arranged on the channel bottom.

[0061] Example 1

[0062] This embodiment includes the following steps:

[0063] Step 1, preparing calcined expanded perlite: heating the expanded perlite to 400°C at a heating rate of 20°C / min and then keeping it warm for 0.5h, then heating to 800°C at a heating rate of 20°C / min and then keeping it warm for 0.5h, then heating to 950°C at a heating rate of 10°C / min and then keeping it warm for 1h, and finally cooling to room temperature to obtain calcined expanded perlite;

[0064] Step 2, prepare a composite phase change energy storage material: propylene glycol, KCl, Al(NO3)3 and H2O in a mass ratio of 1.5:1.0:2.0:5.0 are mixed in a water bath at 60°C, and then 1.5% of SrCl2 in the total mass of propylene glycol, KCl, Al(NO3)3 and H2O is added as a nucleating agent and ultrasonically dispersed for 1 hour to obtain a composite phase change energy storage material;

[0065] Step 3, preparing phase-change expanded perlite: pour the composite phase-change energy storage material obtained in step 2 into a suction filtration bottle and heat it in a water bath at 60°C, then pour the calcined expanded perlite obtained in step 1 into the suction filtration bottle, and then evacuate the suction filtration bottle at a pressure of -0.07MPa for 15min, and finally cool it at room temperature for more than 24h to obtain phase-change expanded perlite;

[0066] Step 4, surface treatment of vitrified microspheres and phase-change expanded perlite: the vitrified microspheres and the phase-change expanded perlite obtained in step 3 are placed in a mixer and stirred at a speed of 50 rpm for 3 minutes, and while stirring, the silane coupling agent KH570 is evenly sprayed on the surface of the phase-change expanded perlite and the vitrified microspheres through an ultrasonic atomizing nozzle. After the spraying is completed, the sprayed vitrified microspheres and the phase-change expanded perlite are taken out and placed in a dryer for aging for more than 48 hours, respectively, to obtain surface-treated vitrified microspheres and surface-treated phase-change expanded perlite;

[0067] Step 5. Preparation of low-temperature phase-change energy storage and thermal insulation mortar: put the glue powder and water into a weightless mixer and stir for more than 60 seconds, then add the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite obtained in step 4 at a speed of 50rpm, stir for 5 minutes, and obtain a low-temperature phase-change energy storage and thermal insulation mortar with a consistency of 80mm; the low-temperature phase-change energy storage and thermal insulation mortar is composed of the following components in parts by mass: 180 parts of glue powder, 130 parts of surface-treated vitrified microspheres and surface-treated phase-change expanded perlite, and the mass ratio of water to glue powder is 0.8:1, and the volume ratio of the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite is 7:3; the glue powder is composed of the following components in parts by mass: 138 parts of cement, 27 parts of fly ash, 9 parts of slaked lime, Wacker latex powder 4015N 1.40 parts, 0.345 parts of hydroxypropyl methylcellulose, 0.136 parts of triethanolamine, 0.36 parts of sodium methyl siliconate, and 0.9 parts of polypropylene fiber.

[0068] After testing, the ternary inorganic-organic composite low-temperature phase change energy storage material prepared in this embodiment has a melting temperature of 4.52°C and a phase change enthalpy of 268.5 J / g. By adding a SrCl2 nucleating agent with a mass fraction of 1.5%, the supercooling of the system can be reduced to 2.25°C. After 200 thermal cycles, the low-temperature phase change energy storage insulation mortar did not produce a large amount of leakage and had good stability. From the perspective of phase change latent heat, after 200 thermal cycles, the low-temperature phase change energy storage insulation mortar maintained a high phase change latent heat characteristic, and the effect of thermal cycles on it was small.

[0069] The low-temperature phase change energy storage insulation mortar prepared in this embodiment effectively improves the problems of supercooling and phase separation, and can control the melting temperature at about 4°C. When the ambient temperature drops to near the freezing point, the phase change material will begin to undergo a phase change to release heat, thereby reducing the damage caused by freezing. It can effectively delay the freezing process and improve the antifreeze performance of the material. This feature is particularly important in applications in cold areas, and can greatly extend the service life of the structure and reduce damage caused by freezing.

[0070] The low-temperature phase change energy storage insulation mortar prepared in this embodiment has a compressive strength of 3.25 MPa and a dry density of 398 kg / m 3 , water absorption is 2.35%, thermal conductivity is 0.0587W·(m·K) -1 , the heat storage coefficient is 20.85W / (m 2 ·K).

[0071] In summary, the low-temperature phase change energy storage insulation mortar prepared in this embodiment has excellent thermal insulation performance, good compressive strength and waterproof performance, as well as the characteristics of being light and easy to construct, and can automatically absorb heat and release heat to effectively resist low temperature environments.

[0072] Example 2

[0073] This embodiment includes the following steps:

[0074] Step 1, preparing calcined expanded perlite: heating the expanded perlite to 400°C at a heating rate of 10°C / min and then keeping it warm for 1 hour, then heating to 800°C at a heating rate of 10°C / min and then keeping it warm for 1 hour, then heating to 850°C at a heating rate of 5°C / min and then keeping it warm for 2 hours, and finally cooling to room temperature to obtain calcined expanded perlite;

[0075] Step 2, prepare a composite phase change energy storage material: propylene glycol, KCl, Al(NO3)3 and H2O in a mass ratio of 1:1.5:2.5:4.5 are mixed in a water bath at 55°C, and then 1% SrCl2 of the total mass of propylene glycol, KCl, Al(NO3)3 and H2O is added as a nucleating agent and ultrasonically dispersed for 0.5h to obtain a composite phase change energy storage material;

[0076] Step 3, preparing phase-change expanded perlite: pour the composite phase-change energy storage material obtained in step 2 into a suction filtration bottle and heat it in a water bath at 50°C, then pour the calcined expanded perlite obtained in step 1 into the suction filtration bottle, and then evacuate the suction filtration bottle at a pressure of -0.06MPa for 20min, and finally cool it at room temperature for more than 24h to obtain phase-change expanded perlite;

[0077] Step 4, surface treatment of vitrified microspheres and phase-change expanded perlite: the vitrified microspheres and the phase-change expanded perlite obtained in step 3 are placed in a mixer and stirred at a speed of 60 rpm for 4 minutes, and while stirring, the silane coupling agent KH550 is evenly sprayed on the surface of the phase-change expanded perlite and the vitrified microspheres through an ultrasonic atomizing nozzle. After the spraying is completed, the sprayed vitrified microspheres and the phase-change expanded perlite are taken out and placed in a dryer for aging for more than 48 hours, respectively, to obtain surface-treated vitrified microspheres and surface-treated phase-change expanded perlite;

[0078] Step 5. Preparation of low-temperature phase-change energy storage and thermal insulation mortar: put the glue powder and water into a weightless mixer and stir for more than 60 seconds, then add the surface-treated vitrified microspheres and surface-treated phase-change expanded perlite obtained in step 4 at a speed of 40rpm, stir for 4 minutes, and obtain a low-temperature phase-change energy storage and thermal insulation mortar with a consistency of 70mm; the low-temperature phase-change energy storage and thermal insulation mortar is composed of the following components in parts by mass: 175 parts of glue powder, 120 parts of surface-treated vitrified microspheres and surface-treated phase-change expanded perlite, and the mass ratio of water to glue powder is 0.7:1, and the volume ratio of the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite is 6:4; the glue powder is composed of the following components in parts by mass: 144 parts of cement, 25.5 parts of fly ash, 8.8 parts of slaked lime, Wacker latex powder 4015N 1.44 parts, 0.34 parts of hydroxypropyl methylcellulose, 0.140 parts of triethanolamine, 0.35 parts of sodium methyl siliconate, and 0.7 parts of polypropylene fiber.

[0079] Example 3

[0080] This embodiment includes the following steps:

[0081] Step 1, preparing calcined expanded perlite: heating the expanded perlite to 400°C at a heating rate of 15°C / min and then keeping it warm for 0.8h, then heating to 800°C at a heating rate of 15°C / min and then keeping it warm for 0.8h, then heating to 1000°C at a heating rate of 7°C / min and then keeping it warm for 1.5h, and finally cooling to room temperature to obtain calcined expanded perlite;

[0082] Step 2, prepare a composite phase change energy storage material: propylene glycol, KCl, Al(NO3)3 and H2O in a mass ratio of 1.8:1.3:2.2:5.8 are heated in a water bath at 50°C for mixing, and then 2% SrCl2 of the total mass of propylene glycol, KCl, Al(NO3)3 and H2O is added as a nucleating agent for ultrasonic dispersion for 0.8h to obtain a composite phase change energy storage material;

[0083] Step 3, preparing phase-change expanded perlite: pour the composite phase-change energy storage material obtained in step 2 into a suction filtration bottle and heat it in a water bath at 55°C, then pour the calcined expanded perlite obtained in step 1 into the suction filtration bottle, and then evacuate the suction filtration bottle at a pressure of -0.05MPa for 10 minutes, and finally cool it at room temperature for more than 24 hours to obtain phase-change expanded perlite;

[0084] Step 4, surface treatment of vitrified microspheres and phase-change expanded perlite: the vitrified microspheres and the phase-change expanded perlite obtained in step 3 are respectively placed in a mixer and stirred at a speed of 40 rpm for 5 minutes, and while stirring, the silane coupling agent KH570 is evenly sprayed on the surface of the phase-change expanded perlite and the vitrified microspheres through an ultrasonic atomizing nozzle. After the spraying is completed, the sprayed vitrified microspheres and the phase-change expanded perlite are taken out and placed in a dryer for aging for more than 48 hours, respectively, to obtain surface-treated vitrified microspheres and surface-treated phase-change expanded perlite;

[0085] Step 5. Preparation of low-temperature phase-change energy storage and thermal insulation mortar: put the glue powder and water into a weightless mixer and stir for more than 60 seconds, then add the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite obtained in step 4 at a speed of 60rpm, stir for 3 minutes, and obtain a low-temperature phase-change energy storage and thermal insulation mortar with a consistency of 90mm; the low-temperature phase-change energy storage and thermal insulation mortar is composed of the following components in parts by mass: 170 parts of glue powder, 125 parts of surface-treated vitrified microspheres and surface-treated phase-change expanded perlite, and the mass ratio of water to glue powder is 0.9:1, and the volume ratio of the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite is 6.5:3.5; the glue powder is composed of the following components in parts by mass: 136 parts of cement, 26 parts of fly ash, 8.5 parts of slaked lime, Wacker latex powder 4015N 1.36 parts, hydroxypropyl methylcellulose 0.36 parts, triethanolamine 0.144 parts, sodium methyl siliconate 0.34 parts, polypropylene fiber 1.0 parts.

[0086] Example 4

[0087] This embodiment includes the following steps:

[0088] Step 1: Sorting and crushing of waste rubber: crushing and separating the waste rubber to obtain rubber powder with a particle size less than 16 mesh;

[0089] Step 2, cleaning: soak the rubber powder obtained in step 1 in clean water for 7 hours, and mechanically stir for 10 minutes every 2.5 hours, then take it out and soak it in 1.5 mol / L NaOH solution for 24 hours, and mechanically stir for 10 minutes every 5 hours, then wash it to neutrality and dry it;

[0090] Step 3: Ultrasonic desulfurization and activation treatment: The rubber powder dried in step 2 is activated by an ultrasonic energy-focusing transducer at a frequency of 50 kHz for 10 minutes, and then aged in a dry environment for 8 hours to obtain desulfurized and activated rubber powder;

[0091] Step 4, preparation of hydrophilic rubber powder: the desulfurized activated rubber powder obtained in step 3 and the polyetherimide solution are mixed in a mass and volume ratio of 1000:300, the unit of mass is g, the unit of volume is mL, wherein the mass of the polyetherimide is 3% of the mass of the desulfurized activated rubber powder, and then heated to 90°C, and stirred at a stirring speed of 150rpm for 5 minutes, and then a modifier is added and stirred for another 40 minutes, and then the product is washed to obtain a hydrophilic rubber powder; the modifier is acrylic acid, sodium methacrylic acid, ammonium persulfate and mercaptopropionic acid; the amount of the modifier is as follows: the mass of acrylic acid is twice the mass of the desulfurized activated rubber powder, the mass of sodium methacrylic acid is 80% of the mass of the desulfurized activated rubber powder, the mass of ammonium persulfate is 2% of the mass of the desulfurized activated rubber powder, and the mass of mercaptopropionic acid is 0.1% of the mass of the desulfurized activated rubber powder;

[0092] Step 5, inorganic encapsulation modification: put the hydrophilic rubber powder obtained in step 4 and the inorganic modified admixture in a volume ratio of 4:1 into an air flow stirring equipment, mix and stir for 15 minutes, and then age for 24 hours to obtain modified rubber powder; the inorganic modified admixture is ultrafine silicon powder, kaolin and phosphorus slag powder in a mass ratio of 3:4:3.

[0093] The test shows that the water contact angle of ordinary rubber powder is about 102°, which is hydrophobic. The water contact angle of the modified rubber powder prepared in this embodiment is about 45°, which is hydrophilic. The contact angle is reduced by 57° compared with the unmodified one, which is a decrease of 55.8%, indicating that the introduction of hydrophilic groups such as -CO-, -OH and -SO3H improves the hydrophilicity of the rubber powder, which is beneficial to improving the interfacial bonding ability of rubber and concrete constituent materials.

[0094] Example 5

[0095] This embodiment includes the following steps:

[0096] Step 1: Sorting and crushing of waste rubber: crushing and separating the waste rubber to obtain rubber powder with a particle size less than 16 mesh;

[0097] Step 2, cleaning: soak the rubber powder obtained in step 1 in clean water for 6 hours, and mechanically stir for 10 minutes every 3 hours, then take it out and soak it in 1.0 mol / L NaOH solution for 24 hours, and mechanically stir for 10 minutes every 4 hours, then wash it to neutrality and dry it;

[0098] Step 3: Ultrasonic desulfurization and activation treatment: The rubber powder dried in step 2 is activated by an ultrasonic energy-focusing transducer at a frequency of 20 kHz for 20 minutes, and then aged in a dry environment for 10 hours to obtain desulfurized and activated rubber powder;

[0099] Step 4, preparation of hydrophilic rubber powder: the desulfurized activated rubber powder obtained in step 3 and the polyetherimide solution are mixed in a mass and volume ratio of 1100:400, the unit of mass is g, the unit of volume is mL, wherein the mass of the polyetherimide is 2% of the mass of the desulfurized activated rubber powder, then heated to 60°C, and stirred at a stirring speed of 170rpm for 4 minutes, then a modifier is added and stirred for 50 minutes, and then the product is washed to obtain a hydrophilic rubber powder; the modifier is acrylic acid, urea, sodium polystyrene sulfonate, ammonium persulfate, and mercaptopropionic acid; the amount of the modifier is as follows: the mass of acrylic acid is 2 times the mass of the desulfurized activated rubber powder, the mass of urea is 1 times the mass of the desulfurized activated rubber powder, the mass of sodium polystyrene sulfonate is 70% of the mass of the desulfurized activated rubber powder, the mass of ammonium persulfate is 2% of the mass of the desulfurized activated rubber powder, and the mass of mercaptopropionic acid is 0.1% of the mass of the desulfurized activated rubber powder;

[0100] Step 5, inorganic encapsulation modification: put the hydrophilic rubber powder obtained in step 4 and the inorganic modified admixture in a volume ratio of 3:1 into an air flow stirring device, mix and stir for 10 minutes, and then age for 24 hours to obtain modified rubber powder; the inorganic modified admixture is ultrafine silicon powder, kaolin and phosphorus slag powder in a mass ratio of 2:4:3.

[0101] Example 6

[0102] This embodiment includes the following steps:

[0103] Step 1: Sorting and crushing of waste rubber: crushing and separating the waste rubber to obtain rubber powder with a particle size less than 16 mesh;

[0104] Step 2, cleaning: soak the rubber powder obtained in step 1 in clean water for 8 hours, and mechanically stir for 10 minutes every 2 hours, then take it out and soak it in 2.0 mol / L NaOH solution for 24 hours, and mechanically stir for 10 minutes every 6 hours, then wash it to neutrality and dry it;

[0105] Step 3: Ultrasonic desulfurization and activation treatment: The rubber powder dried in step 2 is activated by an ultrasonic energy-focusing transducer at a frequency of 30 kHz for 15 minutes, and then aged in a dry environment for 6 hours to obtain desulfurized activated rubber powder;

[0106] Step 4, preparation of hydrophilic rubber powder: the desulfurized activated rubber powder obtained in step 3 and the polyetherimide solution are mixed in a mass and volume ratio of 900:200, the unit of mass is g, the unit of volume is mL, wherein the mass of the polyetherimide is 1% of the mass of the desulfurized activated rubber powder, then heated to 100°C, and stirred at a stirring speed of 200 rpm for 2 minutes, then a modifier is added and stirred for 30 minutes, and then the product is washed to obtain a hydrophilic rubber powder; the modifier is maleic anhydride, sodium methacrylic acid, sodium polystyrene sulfonate and mercaptopropionic acid; the amount of the modifier is such that the mass of maleic anhydride is 1.5 times the mass of the desulfurized activated rubber powder, the mass of sodium methacrylic acid is 80% of the mass of the desulfurized activated rubber powder, the mass of sodium polystyrene sulfonate is 70% of the mass of the desulfurized activated rubber powder, and the mass of mercaptopropionic acid is 0.1% of the mass of the desulfurized activated rubber powder;

[0107] Step 5, inorganic encapsulation modification: put the hydrophilic rubber powder obtained in step 4 and the inorganic modified admixture in a volume ratio of 5:1 into an air flow stirring equipment, mix and stir for 20 minutes, and then age for 24 hours to obtain modified rubber powder; the inorganic modified admixture is ultrafine silicon powder, kaolin and phosphorus slag powder in a mass ratio of 3:3:4.

[0108] Example 7

[0109] This embodiment includes the following steps:

[0110] Step 1: Mix 157 parts of water, 274 parts of cement, 91 parts of fly ash, 730 parts of sand, 1187 parts of crushed stone, 4.380 parts of water reducer, 0.531 parts of air entraining agent and 39 parts of modified rubber powder, pour them in a mold, and then perform curing to obtain a modified rubber concrete precast layer.

[0111] Example 8

[0112] This embodiment includes the following steps:

[0113] Step 1: Mix 157 parts of water, 274 parts of cement, 91 parts of fly ash, 692 parts of sand, 1187 parts of crushed stone, 4.380 parts of water reducer, 0.531 parts of air entraining agent and 77 parts of modified rubber powder to obtain modified rubber concrete, and then pour and cure it in a mold to obtain a modified rubber concrete prefabricated layer.

[0114] Example 9

[0115] This embodiment includes the following steps:

[0116] Step 1: Mix 157 parts of water, 274 parts of cement, 91 parts of fly ash, 654 parts of sand, 1187 parts of crushed stone, 4.380 parts of water reducer, 0.531 parts of air entraining agent and 115 parts of modified rubber powder to obtain modified rubber concrete, then pour it in a mold and perform curing to obtain a modified rubber concrete precast layer.

[0117] Comparative Example 1

[0118] This comparative example comprises the following steps:

[0119] Step 1: Mix 157 parts of water, 274 parts of cement, 91 parts of fly ash, 769 parts of sand, 1187 parts of crushed stone, 4.380 parts of water reducer and 0.531 parts of air entraining agent to obtain rubber concrete, then pour and cure it in a mold to obtain a rubber concrete prefabricated block.

[0120] The raw material amounts of the modified rubber concrete prefabricated layers and rubber concrete prefabricated blocks in Examples 7, 8, 9 and Comparative Example 1 are shown in Table 1.

[0121] Table 1

[0122]

[0123] As can be seen from Table 1, the difference between Examples 7, 8 and 9 is the different amounts of modified rubber powder added, which are 5%, 10% and 15% of the mass of the sand respectively. Comparative Example 1 is the benchmark group without the addition of modified rubber powder.

[0124] The modified rubber concrete, modified rubber concrete prefabricated layer, rubber concrete, and rubber concrete prefabricated block in Examples 7, 8, 9 and Comparative Example 1 were tested. The test results are shown in Table 2.

[0125] Table 2

[0126]

[0127]

[0128] As can be seen from Table 2, the slump results of the modified rubber concrete prepared in Examples 7, 8, and 9 are 180±20 mm, which meets the design requirements. After the modified rubber powder is coated with inorganic powder, the surface pores are filled, which greatly reduces its poor air entrainment effect and improves its disadvantage of easy floating. The modified rubber powder has no adverse effect on the workability and air entrainment performance of the concrete.

[0129] In terms of mechanical properties: compared with comparative example 1, the compressive strength of embodiments 7, 8, and 9 increased by 4.02%, 7.54%, and 1.45%, and the flexural strength increased by 13.80%, 31.03%, and 6.70%. With the increase of the amount of modified rubber powder, the compressive strength and flexural strength of concrete both showed a trend of increasing first and then decreasing. This is because the modified rubber powder has a hydrophilic group and has good compatibility with cement-based materials. The inorganic powder coated on the surface can further improve the interface defects between the rubber powder and the concrete, so as to improve the mechanical properties of the concrete. When the modified rubber powder is added by 15%, the mechanical properties are not significantly improved; the elastic modulus is reduced by 5.07%, 6.76%, and 11.15%, indicating that the modified rubber powder can enhance the toughness and ductility of concrete, and can improve the deformation resistance of the antifreeze and anti-seepage structure of the concrete channel to a certain extent.

[0130] In terms of durability: the impermeability grade is W14; antifreeze performance: after 300 freeze-thaw cycles, the relative dynamic modulus of Examples 7, 8, and 9 increased by 15.23%, 20.96%, and 11.59% respectively compared with Comparative Example 1; the mass decreased by 45.86%, 68.48%, and 42.63% respectively; the antifreeze performance of the modified rubber concrete is greatly improved, because the modified rubber powder, as an elastomer, can absorb the stress generated in the freeze-thaw cycle. When frost heave occurs, the modified rubber powder can be deformed to absorb part of the stress, which plays a buffering role and reduces the damage to the concrete caused by ice crystal formation in the freeze-thaw cycle, thereby reducing the cracking of the concrete caused by volume change, enhancing the toughness and ductility of the concrete, and can improve the deformation resistance of the concrete channel antifreeze and anti-seepage structure to a certain extent.

[0131] Taking all performance and economic factors into consideration, 10% substitution is the optimal dosage, that is, Example 8 is the optimal mix ratio.

[0132] Example 10

[0133] This embodiment includes the following steps:

[0134] Step 1: Mix 155 parts of water, 292 parts of cement, 73 parts of fly ash, 685 parts of sand, 1180 parts of crushed stone, 4.198 parts of water reducer, 0.523 parts of air entraining agent and 45 parts of modified rubber powder, pour them in a mold, and then perform curing to obtain a modified rubber concrete precast layer.

[0135] Embodiment 11

[0136] This embodiment includes the following steps:

[0137] Step 1: Mix 153 parts of water, 281 parts of cement, 82 parts of fly ash, 710 parts of sand, 1190 parts of crushed stone, 4.445 parts of water reducer, 0.517 parts of air entraining agent and 93 parts of modified rubber powder, pour them in a mold, and then perform curing to obtain a modified rubber concrete precast layer.

[0138] Example 12

[0139] This embodiment includes the following steps:

[0140] Step 1: Survey and lay out: Use a total station to survey and lay out, ensure that the points and lines on site are clear, stable, and convenient for construction, and check their accuracy regularly;

[0141] Step 2: Channel base surface treatment: According to the measurement and layout in step 1, the trapezoidal channel is excavated. During the earthwork excavation, the 40cm protective layer reserved is excavated to basically ensure the flatness of the slope. All tree roots, weeds and sharp stones must be removed during the protective layer excavation. During the base surface treatment, drainage facilities within the paving work range must be well prepared. For coarse gravel foundations, a roller must be used to roll and compact the foundation of the channel system building, and the overall density must be no less than 0.6kg / m 3 For soil foundation, compact the original soil and stop when the compaction degree reaches 0.8MPa; set a section every 12m on the trimmed slope, and set 3 points on each section to mark the elevation and pile number; increase the number of piles at river bends, buildings and diameter change locations.

[0142] Step 3: Spread gravel cushion: Spread a 15cm thick gravel cushion in the trapezoidal channel excavated in step 2. Use qualified crushed stone for cushion construction, and the designed paving volume is about 2.20m per linear meter. 3 Unload at the designated location. The cushion material should be laid upward layer by layer from the bottom of the slope. It is forbidden to dump it along the slope. After laying, it should be compacted as necessary to ensure that it meets the requirements of the specifications. The laid cushion layer should be carried out in time for the next block construction. When the temperature is negative, the crushed stone should not be frozen. Stop work and cover it on snowy days. After the snow, the work needs to be cleared of snow and debris;

[0143] Step 4: Arrange anti-seepage and anti-clogging drainage and pressure relief devices: Arrange anti-seepage and anti-clogging drainage and pressure relief devices in the gravel cushion layer laid in step 3. The anti-seepage and anti-clogging drainage and pressure relief devices consist of drainage flower pipes, connecting pressure plates, and anti-clogging check valves (check valve body, link buckles, and construction covers). Water is collected through drainage flower pipes, connecting pressure plates, and water-conducting geomembranes laid under the structural layer, and discharged through the anti-clogging check valve. The connecting pressure plate is a fastening connection and sealing structure when the drainage pipe passes through the geomembrane, which can The anti-seepage performance of the geomembrane penetration point is well guaranteed; two rows of staggered anti-seepage and anti-clogging drainage and pressure relief devices are arranged on each side of the channel slope of the channel anti-freezing and anti-seepage structure, and a row of anti-seepage and anti-clogging drainage and pressure relief devices is arranged in the middle part of the channel bottom of the channel anti-freezing and anti-seepage structure, and the spacing between the anti-seepage and anti-clogging drainage and pressure relief devices in the same row is 12m, and one row of anti-seepage and anti-clogging drainage and pressure relief devices on each side of the channel slope is 55cm high from the slope foot, and the other row is 55cm below the normal water level of the channel;

[0144] Step 5. Laying and splicing one-way drainage composite geomembrane: Lay and splice one-way drainage composite geomembrane with a thickness of 2mm on the gravel cushion layer after arranging the anti-seepage, anti-clogging and drainage pressure relief device in step 4. The geomembrane is laid from top to bottom, and the top of the slope is pressed with heavy objects to prevent slipping. Avoid strong pulling and tearing during laying to ensure that the geomembrane is laid flat and appropriately tight to ensure that it fits the slope surface flatly. The geotextile needs to be embedded in the foot guard and the top pressure concrete, and is divided into three sections, namely the foot guard section, the middle section and the top pressure section. The overlap of each section is not less than 10cm. The one-way drainage composite geomembrane is welded by hot melt welding. The fastening connection and sealing structure with the connecting pressure plate must be well done to ensure waterproofness. Mechanical rolling or human damage is prohibited during and after the process. Damage needs to be replaced or repaired immediately. After paving, follow-up construction should be carried out in time to avoid the geomembrane from being exposed to the sun for more than two days;

[0145] Step 6: Apply low-temperature phase-change energy storage insulation mortar: Apply a 10-cm-thick low-temperature phase-change energy storage insulation mortar on the spliced ​​one-way drainage composite geomembrane laid in step 5. After the construction is completed, when no liquid flows out on it, immediately cover it with a plastic film and a layer of sack for curing. After curing for 3 days, proceed to the next step;

[0146] Step 7. Spread the modified rubber concrete precast layer: First, evenly apply a 2mm thick layer of M20 polymer cement-based waterproof leveling mortar on the surface of the low-temperature phase change energy storage insulation mortar applied in step 6 to ensure the flatness and waterproof performance of the base layer. Then carry out measurement and layout work, accurately set a control section every 15m along the center line of the river channel, and set up control piles at key positions such as the foot guard, slope center and pressure top to provide positioning basis for subsequent precise construction. Then, use a 10t truck crane to hoist the 10.0cm thick modified rubber concrete precast layer onto the leveling mortar, and ensure the close fit between the blocks through manual paving. The bonding also uses M20 polymer cement-based waterproof leveling mortar. The cross-section is designed as an arc-bottom trapezoid with a slope angle of 70° and a slope ratio of 1:1.75. , when laying, start from the foot guard from bottom to top, use the tension line to strictly control the slope from the foot guard to the top of the pressure to ensure the accuracy of the starting slope. In special parts such as river bends and anchor beams, adopt the staggered connection method of first laying the outer layer and then laying the inner layer to avoid the appearance of through seams and maintain the flatness and beauty of the overall structure. During the laying of prefabricated blocks, the longitudinal and transverse gaps must be controlled within the range of 5mm to 7mm to ensure that the flatness per meter does not exceed 5mm. For special parts such as anti-seepage, anti-clogging, drainage and pressure relief devices, additional waterproofing treatment is required, and polyvinyl chloride mastic is filled to enhance the waterproof effect. In order to prevent the channel concrete structure from cracking due to temperature stress, a 2cm to 3cm wide expansion joint is set every 6m, and polyvinyl chloride mastic is filled in the joint to ensure the stability and durability of the entire structure;

[0147] Step 8: Surface inspection and anti-seepage treatment: Check the surface cracks and bonding joints of the modified rubber concrete prefabricated layer paved in step 7, and apply polyvinyl chloride glue to the defective parts to ensure the integrity of the entire structure and improve the anti-seepage and waterproof properties;

[0148] Step 9. Maintenance and acceptance: The structure coated with polyvinyl chloride mortar in step 8 is maintained for 28 days, and then the external dimensions, contour straightness, surface flatness, longitudinal slope of the channel bottom centerline, channel slope and channel bottom lining appearance, deformation joints, structural joints and other factors are inspected to obtain a channel antifreeze and anti-seepage structure containing phase change insulation materials and modified rubber concrete.

[0149] Embodiment 13

[0150] The difference between this embodiment and Embodiment 12 is that the thickness of the gravel cushion layer is 10 cm, the thickness of the one-way drainage composite geomembrane is 3 mm, the thickness of the low-temperature phase change energy storage insulation mortar is 6 cm, the thickness of the leveling mortar is 3 mm, and the thickness of the modified rubber concrete precast layer is 7.0 cm; and the spacing between the anti-seepage and anti-siltation drainage and pressure relief devices in the same row is 10 m, and one row of anti-seepage and anti-siltation drainage and pressure relief devices on each side of the channel slope is 60 cm high from the slope foot, and the other row is 50 cm below the normal water level of the channel.

[0151] Embodiment 14

[0152] The difference between this embodiment and Embodiment 12 is that the thickness of the gravel cushion layer is 20 cm, the thickness of the one-way drainage composite geomembrane is 2.5 mm, the thickness of the low-temperature phase change energy storage insulation mortar is 8 cm, the thickness of the leveling mortar is 2.5 mm, and the thickness of the modified rubber concrete precast layer is 9.0 cm; and the spacing between the anti-seepage and anti-siltation drainage and pressure relief devices in the same row is 15 m, and one row of anti-seepage and anti-siltation drainage and pressure relief devices on each side of the channel slope is 50 cm high from the slope foot, and the other row is 60 cm below the normal water level of the channel.

[0153] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete, characterized in that: The channel antifreeze and anti-seepage structure has an arc-bottom trapezoidal cross-section and includes 5 layers, which are, from bottom to top, a gravel cushion layer, a one-way drainage composite geomembrane, a low-temperature phase change energy storage insulation mortar, a leveling mortar and a modified rubber concrete precast layer; the channel antifreeze and anti-seepage structure is penetrated by multiple rows of anti-seepage, anti-clogging and drainage and pressure relief devices.

2. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 1, characterized in that: The thickness of the gravel cushion layer is 10cm-20cm, the thickness of the unidirectional drainage composite geomembrane is 2mm-3mm, the thickness of the low-temperature phase change energy storage insulation mortar is 6cm-10cm, the thickness of the leveling mortar is 2mm-3mm, the thickness of the modified rubber concrete prefabricated layer is 7.0cm-10.0cm, and the modified rubber concrete prefabricated layer includes a channel slope prefabricated block arranged on the channel slope and an arc-shaped channel bottom prefabricated block arranged on the channel bottom; two rows of staggered anti-seepage, anti-siltation and drainage pressure relief devices are arranged on each side of the channel anti-freezing and anti-seepage structure, a row of anti-seepage, anti-siltation and drainage pressure relief devices is arranged in the middle part of the channel bottom of the channel anti-freezing and anti-seepage structure, and the spacing between the anti-seepage, anti-siltation and drainage pressure relief devices in the same row is 10m-15m, and one row of anti-seepage, anti-siltation and drainage pressure relief devices on each side of the channel slope is 50cm-60cm high from the slope foot, and the other row is 50cm-60cm below the normal water level of the channel.

3. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 1, characterized in that: The preparation method of the low-temperature phase-change energy storage thermal insulation mortar comprises the following steps: Step 1, preparing calcined expanded perlite: calcining the expanded perlite in stages to obtain calcined expanded perlite; Step 2, preparing a composite phase change energy storage material: heating propylene glycol, KCl, Al(NO3)3 and H2O in a water bath and blending them, then adding SrCl2 as a nucleating agent and performing ultrasonic dispersion to obtain a composite phase change energy storage material; Step 3, preparing phase-change expanded perlite: pouring the composite phase-change energy storage material obtained in step 2 into a suction filtration bottle and heating it in a water bath, then pouring the calcined expanded perlite obtained in step 1 into the suction filtration bottle, and then vacuumizing the suction filtration bottle, and finally cooling it at room temperature to obtain phase-change expanded perlite; Step 4, surface treatment of vitrified microspheres and phase-change expanded perlite: the vitrified microspheres and the phase-change expanded perlite obtained in step 3 are placed in a mixer for stirring respectively, and while stirring, the silane coupling agent is evenly sprayed on the surface of the phase-change expanded perlite and the vitrified microspheres through an ultrasonic atomizing nozzle. After the spraying is completed, the sprayed vitrified microspheres and the phase-change expanded perlite are taken out and placed in a dryer for aging respectively, to obtain surface-treated vitrified microspheres and surface-treated phase-change expanded perlite respectively; Step 5. Preparation of low-temperature phase-change energy storage and thermal insulation mortar: Put the glue powder and water into a weightless mixer and stir for more than 60 seconds, then add the surface-treated vitrified microspheres and surface-treated phase-change expanded perlite obtained in step 4 at a speed of 40rpm to 60rpm, stir for 3min to 5min, and obtain a low-temperature phase-change energy storage and thermal insulation mortar with a consistency of 70mm to 90mm; the low-temperature phase-change energy storage and thermal insulation mortar is composed of the following components in parts by mass: glue powder 170-180 parts, surface-treated vitrified microspheres and surface-treated phase-change expanded perlite 120-130 parts, the mass ratio of water to rubber powder is 0.7-0.9:1, and the volume ratio of the surface-treated vitrified microspheres and the surface-treated phase-change expanded perlite is 6-7:3-4; the rubber powder is composed of the following components in mass parts: 136-144 parts of cement, 25.5-27 parts of fly ash, 8.5-9 parts of slaked lime, 1.36-1.44 parts of Wacker latex powder 4015N, 0.34-0.36 parts of hydroxypropyl methylcellulose, 0.136-0.144 parts of triethanolamine, 0.34-0.36 parts of sodium methyl siliconate, and 0.7-1.0 parts of polypropylene fiber.

4. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 3, characterized in that: The process of the staged calcination in step 1 is: heating to 400°C at a heating rate of 10°C / min to 20°C / min, then keeping warm for 0.5h to 1h, then heating to 800°C at a heating rate of 10°C / min to 20°C / min, then keeping warm for 0.5h to 1h, then heating to 850°C to 1000°C at a heating rate of 5°C / min to 10°C / min, then keeping warm for 1h to 2h, and finally cooling to room temperature.

5. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 3, characterized in that: In step 2, the mass ratio of glycerol, KCl, Al(NO3)3 and H2O is 1-1.5:1.0-1.5:2.0-2.5:4.5-5.8, the amount of SrCl2 added is 1%-2% of the total mass of glycerol, KCl, Al(NO3)3 and H2O, the temperature of the water bath heating blending is 50°C-60°C, and the time of the ultrasonic dispersion is 0.5h-1h.

6. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 3, characterized in that: In step 3, the water bath heating temperature is 50° C. to 60° C., the vacuuming pressure is -0.05 MPa to -0.07 MPa, the time is 10 min to 20 min, and the cooling time is more than 24 h.

7. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 3, characterized in that: In step 4, the stirring speed is 40 rpm to 60 rpm, the time is 3 min to 5 min, the silane coupling agent is KH550 or KH570, and the aging time is more than 48 h.

8. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 1, characterized in that: The modified rubber concrete prefabricated layer is made of the following components in parts by mass: 153-157 parts of water, 274-292 parts of cement, 73-91 parts of fly ash, 654-730 parts of sand, 1180-1190 parts of crushed stone, 4.198-4.445 parts of water reducer, 0.517-0.531 parts of air entraining agent and 39-115 parts of modified rubber powder.

9. The channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete according to claim 8, characterized in that: The preparation method of the modified rubber powder comprises the following steps: Step 1: Sorting and crushing of waste rubber: crushing and separating the waste rubber to obtain rubber powder with a particle size less than 16 mesh; Step 2, cleaning: soak the rubber powder obtained in step 1 in clean water for 6h to 8h, and mechanically stir for 10min every 2h to 3h, then take it out and soak it in 1.0mol / L to 2.0mol / L NaOH solution for 24h, and mechanically stir for 10min every 4h to 6h, then wash it to neutrality and dry it; Step 3, ultrasonic desulfurization activation treatment: the rubber powder dried in step 2 is activated by an ultrasonic energy-focusing transducer at a frequency of 20kHz to 50kHz for 10min to 20min, and then aged in a dry environment for 6h to 10h to obtain desulfurized activated rubber powder; Step 4, preparation of hydrophilic rubber powder: the desulfurized activated rubber powder obtained in step 3 and the dispersant solution are mixed at a mass and volume ratio of 900-1100:200-400, the mass unit is g, and the volume unit is mL, wherein the mass of the dispersant is 1%-3% of the mass of the desulfurized activated rubber powder, and then heated to 60°C-100°C, and stirred at a stirring speed of 150rpm-200rpm for 2min-5min, then a modifier is added, stirred for 30min-50min, and the product is washed to obtain hydrophilic rubber powder; the modifier is three or more of maleic anhydride, acrylic acid, sodium methacrylic acid, urea, sodium polystyrene sulfonate, ammonium persulfate, and mercaptopropionic acid; Step 5, inorganic encapsulation modification: put the hydrophilic rubber powder obtained in step 4 and the inorganic modified admixture in a volume ratio of 3 to 5:1 into an air flow stirring device, mix and stir for 10 to 20 minutes, and then age for 24 hours to obtain modified rubber powder; the inorganic modified admixture is ultrafine silicon powder, metakaolin and phosphorus slag powder in a mass ratio of 2 to 3:3 to 4:3 to 4.

10. A construction method for a channel antifreeze and anti-seepage structure containing a phase change thermal insulation material and modified rubber concrete as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: Step 1: Measure and lay out: Use a total station to measure and lay out; Step 2: Channel base surface treatment: excavate a trapezoidal channel according to the measurement and layout in step 1; Step 3: Laying gravel cushion layer: Laying gravel cushion layer in the trapezoidal channel excavated in step 2; Step 4: Arrange anti-seepage and anti-clogging drainage and pressure relief devices: Arrange anti-seepage and anti-clogging drainage and pressure relief devices in the gravel cushion layer laid in step 3; Step 5: Laying and splicing one-way drainage composite geomembrane: Laying and splicing one-way drainage composite geomembrane on the gravel cushion after the anti-seepage, anti-clogging and drainage pressure relief device is arranged in step 4; Step 6: Apply low-temperature phase-change energy storage thermal insulation mortar: Apply low-temperature phase-change energy storage thermal insulation mortar on the spliced ​​one-way drainage composite geomembrane laid in step 5; Step 7: Spread the modified rubber concrete prefabricated layer, apply leveling mortar on the low-temperature phase change energy storage insulation mortar applied in step 6, and then spread the modified rubber concrete prefabricated layer on the leveling mortar; Step 8: Surface inspection and anti-seepage treatment: Inspect the prefabricated modified rubber concrete layer spread in step 7, and apply polyvinyl chloride glue to the defective parts; Step nine, maintenance and acceptance: the structure coated with polyvinyl chloride mortar in step eight is maintained, and then accepted to obtain a channel antifreeze and anti-seepage structure containing phase change insulation material and modified rubber concrete.

Citation Information

Patent Citations

  • Thermal insulation building mortar and preparation process thereof

    CN101759416A

  • Cement paste toughening agent and application of cement paste toughening agent in preparation of cementing flexible cement paste

    CN103305197A

  • Anti-freezing anti-seepage anti-cracking concrete and preparation method thereof

    CN110256023A

  • Double-component modified inorganic terrace coating

    CN110499048A

  • Environment-friendly anti-freezing concrete and preparation method thereof

    CN113149541A